Evidence for the Higgs boson decay to a bottom quark-antiquark pair - KAYA, MİTHAT (ELSEVIER, 2018)
A search for the standard model (SM) Higgs boson (H) decaying to b(b)over-bar when produced in association with an electroweak vector boson is reported for the following processes: Z(vv)H, W(mu v)H, W(ev)H, Z(mu mu)H, and Z(ee)H. The search is performed in data samples corresponding to an integrated luminosity of 35.9 f (-1) at root s = 13 TeV recorded by the CMS experiment at the LHC during Run 2 in 2016. An excess of events is observed in data compared to the expectation in the absence of a H -> b(b)over-bar, signal. The significance of this excess is 3.3 standard deviations, where the expectation from SM Higgs boson production is 2.8. The signal strength corresponding to this excess, relative to that of the SM Higgs boson production, is 1.2 +/- 0.4. When combined with the Run 1 measurement of the same processes, the signal significance is 3.8 standard deviations with 3.8 expected. The corresponding signal strength, relative to that of the SM Higgs boson, is 1.06(-0.29)(+0.31). (C) 2018 The Author(s). Published by Elsevier B.V.
Keywords: CMS; Physics; Higgs; BROKEN SYMMETRIES; CROSS-SECTION; HADRON; PARTICLES; STRAHLUNG; PROGRAM; MODEL; MASS